Making experimental data tables in the life sciences more FAIR: a pragmatic approach. Issue 12 (15th December 2020) - Jacob, Daniel; David, Romain; Aubin, Sophie; Gibon, Yves
Abstract: Making data compliant with the FAIR Data principles (Findable, Accessible, Interoperable, Reusable) is still a challenge for many researchers, who are not sure which criteria should be met first and how. Illustrated with experimental data tables associated with a Design of Experiments, we propose an approach that can serve as a model for research data management that allows researchers to disseminate their data by satisfying the main FAIR criteria without insurmountable efforts. More importantly, this approach aims to facilitate the FAIR compliance process by providing researchers with tools to improve their data management practices.